Career Advancement Discrimination Towards Technopreneurial Women in Malaysia - Ooi, Eunice; Lee, Kar Ling (INTI International University, 2021)
3 hypotheses are drawn based on previous academic studies and will be tested out in a survey questionnaire. The fundamental theory of this research will be based of the social role, stigma, career advancement theory. The purpose of this study is to explore the relationship between Discrimination and how it affects career advancement towards technopreneurial women in the Malaysian workplace. This discrimination is explored from the aspect of pay wage gap, motherhood penalty, gender roles and stigmatization. Research done by Khazanah Research Institute in recent years shows that half of Malaysian work force are women and therefore there is a need to understand the forms of discriminations is still happening among working women. This research’s study using quantitative methods based on descriptive research, where convenience sampling is used for the study. Self-administered online questionnaires will be distributed to 400 individuals to find significant relationship between discrimination in career advancement among women and pay wage gap, motherhood penalty and gender roles and stigmatization. This research focuses on cross-sectional analysis that employs methodological approaches focused on descriptive research. The results revealed that pay wage gap, motherhood penalty and gender roles and stigmatizations all have a positive significant relationship with discrimination in career advancement against working women in Malaysia.